Sequential combination chemotherapy consisting of vincristine, peplomycin, methotrexate, cis-diamminedichloroplatinum (II) and adriamycin in urothelial cancer - Konami, T (Hinyokika kiyo. Acta urologica Japonica, 1989)
The VPM-CisA (vincristine (VCR), peplomycin (PLM), methotrexate (MTX), cisplatin (CDDP) and doxorubicin (ADM), regimen was used to treat 33 patients with urothelial tract tumors. Twenty-two patients had bi-dimensionally measurable disease parameters and 11 patients with locally advanced tumors were given postoperative adjuvant chemotherapy. The protocol consisted of 0.6 mg/m2 VCR on days 1 and 3, 3 mg/m2 PLM on days 1 to 4, 3 mg/m2 MTX on days 2 and 4, 35 mg/m2 CDDP on day 4, and 20 mg/m2 ADM on day 5. These doses were adjusted for each case: the above mentioned dose x [(80/(40+Age]2 +[(Karnofsky's performance status/100)2]. Of these patients, 28 (86 percent) were treated adequately, including 8 (36 per cent) who achieved a complete (2) or partial (6) remission. The mean duration of survival was 65.2 weeks for complete and partial responders, and 48.8 weeks for non-responders, which was not a statistically significant difference. Of 11, who were given post-operative adjuvant chemotherapy (mean observation period: 83.5 weeks) 9 were alive without evidence of disease, 1 had a recurrence 8 months after first chemotherapy, 1 died due to pulmonary and liver metastasis 2 years after the chemotherapy. Toxicity included mild myelosupression, moderate anorexia, vomiting, and severe gastric ulcer, pulmonary fibrosis